25-year neuroimaging research on spoken language processing: a bibliometric analysis - Zheng, Yuxuan; Zhang, Boning (Frontiers in Human Neuroscience, 2024)
IntroductionSpoken language processing is of huge interest to cognitive and neural scientists, as it is the dominant channel for everyday verbal communication. The aim of this study is to depict the dynamics of publications in the field of neuroimaging research on spoken language processing between 2000 and 2024.MethodsA bibliometric analysis was conducted to probe this particular subject matter based on data retrieved from Web of Science. A total of 8,085 articles were found, which were analyzed together with their authors, journals of publication, citations and countries of origin.ResultsResults showed a steady increase of publication volume and a relatively high academic visibility of this research field indexed by total citations in the first 25 years of the 21st century. Maps of frequent keywords, institutional collaboration network show that cooperations mainly happen between institutions in the United States, the United Kingdom and Germany. Future trends based on burst detection predict that classification, Alzheimer’s disease and oscillations are potential hot topics.DiscussionPossible reasons for the result include the aging of the population in developed countries, and the rapid growth of artificial intelligence in the past decade. Finally, specific research avenues were proposed which might benefit future studies.